An Iteration Method for Incompressible Viscous/Inviscid Coupled Problem via a Spectral Approximation (Journal of Computational Mathematics, 1999)
An efficient iteration-by-subdomain method (known as the Schwarz alternating algorithm) for incompressible viscous/inviscid coupled model is presented. Appropriate spectral collocation approximations are proposed. The convergence analysis shows that the iterative algorithms converge with a rate independent of the polynomial degree used.
Keywords: Coupled equations; Navier-Stokes equations; Euler equations; Cllocation approximation; Schwarz alternating algorithm.